Problems of research and training in small islands without a social science faculty - Collinwood, Dean Walter (UNESCO, 1982)
This paper describes the experience of the Bahamas in establishing social science research and training programmes. It identifies the problems that arose largely as a result of internal governmental policies and decisions, and highlights some of the external impediments to social science programmes in the Caribbean
Keywords: Social science education